2012
DOI: 10.1016/j.jdeveco.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Social contracts, markets and efficiency: Groundwater irrigation in North India

Abstract: This paper uses primary data to analyze the institutions and informal markets that govern groundwater allocation in a sugarcane-cultivating village in North India. We find that, in contrast to earlier literature, the observed water trades result in efficient water allocation across farms. We interpret this and other stylized facts in terms of a social contract using a simple bargaining model with limited inter-player transfers. Poor functioning of the power sector leads to reduced pumping and a water supply co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
(20 reference statements)
1
19
1
Order By: Relevance
“…In fact, the rate at which water is sold is usually equal to the internal rate at which informal water cooperatives sometime charge their own members as a means to recover their collective expenses (power bill and maintenance costs). This sort of a social contract is also observed by Banerji, Meenakshi, and Khanna (2012) in another part of India. Many well owners also reported a social obligation to provide their neighboring water buyers with an adequate supply of water in order to maintain a long-standing relationship.…”
Section: Discussionsupporting
confidence: 66%
“…In fact, the rate at which water is sold is usually equal to the internal rate at which informal water cooperatives sometime charge their own members as a means to recover their collective expenses (power bill and maintenance costs). This sort of a social contract is also observed by Banerji, Meenakshi, and Khanna (2012) in another part of India. Many well owners also reported a social obligation to provide their neighboring water buyers with an adequate supply of water in order to maintain a long-standing relationship.…”
Section: Discussionsupporting
confidence: 66%
“…Last, these markets help the society by minimizing investments in groundwater due to availability of groundwater in the water market. Banerji et al (2012) find that, in contrast to earlier literature, the observed water trades result in efficient water allocation across farms. Acharyya (2012) suggests changes in the existing institutions of irrigation in India for generating efficiency and proper groundwater irrigation management.…”
Section: Review Of Literaturecontrasting
confidence: 99%
“…Somanathan and Ravindranath (2006) estimate marginal values of water and its elasticity of demand using data on water transactions in a watershed in southern India. Banerji, Meenakshi and Khanna (2012) show that a combination of water rationing and village-level mechanism of water sales can lead to a great misallocation of water across plots and result in large crop losses for plots irrigated from purchased water. Mukherji (2007b) discusses two case studies of alternative institutional arrangements, the kinship group-owned electric submersible tube well and private water market with price regulation by panchayat.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For instance, Banerji et al (2012) provide an example of existence of efficient informal water markets and social institutions that exist in North Indian sugarcane farming communities. Besides a collective arrangement, there exist alternate arrangements in farming communities for mitigating water shortages and managing excess water demand.…”
Section: Model Outlinementioning
confidence: 99%
“…Besides a collective arrangement, there exist alternate arrangements in farming communities for mitigating water shortages and managing excess water demand. For instance, Banerji et al (2012) provide an example of existence of efficient informal water markets and social institutions that exist in North Indian sugarcane farming communities. These farmers buy and sell water based upon their spatial locations, and the price and the amount of water exchanged is determined using the N-player Nash bargaining game.…”
Section: Model Outlinementioning
confidence: 99%